CLINICAL PROFILE AND SPIROMETRIC FINDINGS IN PATIENTS HAVING OBSTRUCTIVE SLEEP APNOEA: A PROSPECTIVE STUDY - SAIFUDDIN, MOHAMMED; DUBEY, PARIKSHIT KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of the study are as follows: (1) To study the clinical profile of patients with OSA. (2) To assess the prevalence of spirometric abnormalities in obstructive sleep apnea (OSA). Methods: This was a prospective study in which 50 patients with OSA were included on the basis of a predefined inclusion and exclusion criteria. Written informed consent was obtained from the participants. Demographic data such as age, gender, weight, height, and BMI were recorded. Severity of OSA was diagnosed on the basis of Apnea-Hypoapnea index. Presenting complaints were analyzed. Spirometry was done in all the cases and disease pattern such as obstructive or restrictive was determined. SSPS 21.0 software was used for statistical analysis and p<0.05 was taken as statistically significant. Results: Among the 50 studied cases, there were 36 (72 %) males and 14 (28.00%) females with a M: F ratio of 1: 0.38. The mean age of the studied cases was found to be 50.04±13.58 years. majority of the patients presenting with obstructive sleep apnea were either obese (64.00%) or overweight (26.00%). OSA was found to be mild, moderate, and severe in 27 (54.00 %), 18 (36.00%), and 5 (10.00 %) patients, respectively. snoring (100%) followed by disturbed sleep or difficulty falling asleep 32 (64%) were most common presenting complaints. Overall abnormal spirometry findings were seen in 35 (70%) patients. Conclusion: Snoring and sleep disturbance are the common presenting complaints in patients with OSA. A significant number of patients with OSA are found to have spirometric abnormalities.